Heterotopic gastric mucosa in the second part of the duodenum causing hemorrhage in a child: a case report and literature review - Huang, Qin; Liu, Lin; Zhan, Lu; Zhu, Yuanlu; Deng, Quanmin (Frontiers in Pediatrics, 2025)
Heterotopic gastric mucosa (HGM) refers to the presence of histologically normal gastric tissue in ectopic anatomical locations. HGM is commonly found in the esophagus, duodenal bulb, and Meckel's diverticulum, but its occurrence in the second part of the duodenum is exceedingly rare. HGM may present with gastrointestinal bleeding, obstruction, or intussusception, with painless bleeding often being the initial symptom, which may progress to hemorrhagic shock. We report a case of a child with HGM in the anatomical part of the duodenum (second part) complicated by hemorrhage, managed at Deyang People's Hospital, along with a literature review.